IDENTIFIKASI DNA LEPTOSPIRA SP PADA SAMPEL AIR DAN TANAH DI KOTA MAKASSAR - Mursalim, Muhammad Fadhlullah; Hatta, Mochammad (Fakultas Farmasi UMI, 2018)
Leptospirosis is a zoonotic disease that can be found all over the world, caused by a pathogenic leptospira genus. This study aims to identify the presence of Leptospira bacterial DNA in water and soil at several locations in Makassar. This research was conducted in microbiology laboratory Faculty of Medicine Hasanuddin University. A total of 16 samples were taken consisting of water and soil samples taken from four locations in Makassar City namely eggplant market, slums, TPA (final landfill) tamangappa and slaughterhouse (RPH). Samples were then tested using the nested RT-PCR method . The results of this study showed that from 16 samples tested showed one sample with positive to the presence of Leptospira sp bacteria obtained from the soil found in slums located in makassar.